Managing ethical risks of machine learning and artificial intelligence : An exploratory study - Vaiste, Juho (fi=Turun yliopisto|en=University of Turku|, 2018)
Machine learning and artificial intelligence are widely recognized to reshape various fields in our societies and business environments. In addition to discovering the possible positive impacts, a multidisciplinary discourse and research about ethical risks and concerns related to the emerging technologies should take place. The research problem is how businesses should consider and manage the ethical risks related to the machine learning and artificial intelligence technologies. The supporting research questions are about identification of the ethical risks, concrete actions and processes for solving the risks, and responsibility in managing ethical risks. The literature review divides into two parts. The first part presents the theoretical background for the work including 1) Artificial intelligence, machine learning and their applications 2) Ethics, business ethics, corporate social responsibility 3) The definition of risk and ethical risk, and risk management. The other part introduces the earlier literature and reports of the ethical risks linked to the emerging technologies. The research section is based on the interviews of the Finnish artificial intelligence and machine learning experts. The principal target group is the technology vendors, and altogether ten interviews present insight to the contemporary view and situation regarding ethical risks in the vendor companies. The interview data was analyzed by comparing the interview results with the earlier reports of AI ethics. The results divide to three categories: 1) Strengthening the view of the earlier reports 2) Providing insight to the practical work related to ethical risks 3) Presenting dissimilarities between the interview results and the earlier reports. The conclusions include theoretical and managerial implications. A theoretical model for technological responsibility combines ethics and risk management. A conceptual framework for a categorization of ethical risks in machine learning and artificial intelligence helps to identify the ethical risks and their different layers. The adoption of technological responsibility is the essential proposal for managerial implications.